IMPLEMENTATION OF EFFECTIVE CONTRACTS IN HEALTH ORGANIZATION: PROBLEMS AND THEIR CONDITIONS FOR OVERCOMING - T. Kozeeva; V. Konovalova (Вестник университета)
The features of effective implementation of contracts in the context of improving the wages in health care organizations. A review of the main problems identified during the implementation of effective contracts. Obtained conditions of applicability of the effective contracts relevant to healthcare organizations. Formulated guidelines for the justification of the performance indicators of staff.